Novel Desmin Mutation Causing Myofibrillar Myopathy in a Hmong Family - Nicolau, Stefan; Howe, Benjamin M.; Naddaf, Elie (Frontiers in Neurology, 2020)
Myofibrillar myopathies (MFM) are a clinically and genetically heterogenous group of inherited myopathies characterised by aggregation of Z-disc proteins. Mutations in desmin account for approximately 7% of MFM. We report here a Hmong family with an autosomal dominant MFM caused by a novel variant in the desmin gene. The proband presented with lower limb followed by upper limb weakness starting in the 5th decade. On examination, there was distal more than proximal muscle weakness. One sibling was similarly affected, while another had an asymptomatic elevation of creatine kinase. Genetic testing revealed a novel p.Ser13Tyr variant, which was predicted by in silico algorithms to alter protein function. Muscle biopsy revealed a MFM. Muscle MRI demonstrated selective involvement of the tensor fasciae latae, semitendinosus, sartorius, gracilis, gastrocnemius, soleus and peroneus longus muscles. In this family, the histological and MRI findings assisted in the interpretation of genetic testing results.